Assessing acute psychological distress in the immediate aftermath of stroke. (February 2018) - Juth, Vanessa; Chan, Michelle K; Cramer, Steven C; Holman, E Alison
Background and purpose: High acute stress may presage the development of subsequent cardiovascular ailments. Understanding how best to assess acute stress may inform early interventions seeking to prevent long-term morbidity/mortality following stroke. A mixed methods approach examined early post-stroke acute stress symptoms using the post-traumatic stress disorder checklist-5 (PCL-5) and the acute stress disorder scale (ASDS). Methods: A focus group of stroke survivors and/or their caregivers ( N =8) evaluated PCL-5/ASDS feasibility, and 20 patients hospitalized for acute stroke were interviewed 2–10 days post-stroke onset, using either the PCL-5 or the ASDS. Results: Acute stress symptoms were present and measurable during acute stroke recovery. Assessment of acute stress in hospitalized patients with stroke is feasible; a briefer modified ASDS has advantages over the PCL-5. Conclusions: The ASDS is a viable and useful measure for assessing psychological distress during the acute post-stroke aftermath. Findings suggest that acute stress symptoms are present among patients with stroke, warranting greater attention to psychological responses in the early post-stroke period. Given that acute stress has serious potential long-term health consequences, additional research on stroke-related acute stress may prove useful for understanding post-stroke morbidity/mortality.